2023
DOI: 10.1111/chso.12739
|View full text |Cite
|
Sign up to set email alerts
|

Does the early childhood education and care in India contribute to children's skill development?

Abstract: Early childhood education and care (ECEC) is a crucial intervention because of its long‐term impact on child development. However, information concerning the effectiveness of the ECEC in developing countries like India is sparsely available. This empirical study drew upon primary data collected from India's eastern state, West Bengal and investigated whether attending preschool contributed to children's cognitive and social skill development. The study found that attending preschool did not provide dividends i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…It means mothers with higher education had children with higher cognitive skills, whereas the mothers with less education had less skilled children. This finding agreeing on significant role of mother's education on children's cognitive development is supported by the findings of many studies that showed statistically significant association between maternal education and children's cognitive ability (Ajayi et al, 2017;Aturupane et al, 2013;Bogale et al, 2013;Duncan & Magnuson, 2012;Firkowska et al, 1978;Ghosh, 2023;Kaplan et al, 2001;Muñez et al, 2022;Warsito et al, 2012). Thus, mother's education is a potent factor for children's cognitive development.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It means mothers with higher education had children with higher cognitive skills, whereas the mothers with less education had less skilled children. This finding agreeing on significant role of mother's education on children's cognitive development is supported by the findings of many studies that showed statistically significant association between maternal education and children's cognitive ability (Ajayi et al, 2017;Aturupane et al, 2013;Bogale et al, 2013;Duncan & Magnuson, 2012;Firkowska et al, 1978;Ghosh, 2023;Kaplan et al, 2001;Muñez et al, 2022;Warsito et al, 2012). Thus, mother's education is a potent factor for children's cognitive development.…”
Section: Discussionsupporting
confidence: 82%
“…However, the association of parent and teacher characteristics with children's cognitive development shows mixed results. Parental education positively predicts their children's cognitive outcomes (Ajayi et al, 2017;Aturupane et al, 2013;Ghosh, 2023;Sania et al, 2019;Singh & Mukherjee, 2017). But mother's influence on the children's cognitive development is the most powerful than fathers (Ajayi et al, 2017;Bogale et al, 2013;Emerson et al, 2018;Flôres et al, 2019;Kaplan et al, 2001;Muñez et al, 2022;Sania et al, 2019;Warsito et al, 2012).…”
Section: Introductionmentioning
confidence: 99%